2016
DOI: 10.1111/vec.12541
|View full text |Cite
|
Sign up to set email alerts
|

An in vitro comparison of the effects of voluven (6% hydroxyethyl starch 130/0.4) and hespan (6% hydroxyethyl starch 670/0.75) on measures of blood coagulation in canine blood

Abstract: Dilution of WB with HES 670/0.75 and HES 130/0.4 resulted in changes in primary and secondary hemostasis. Although there were small differences between saline and HES 670/0.75, no differences between HES solutions were evident in this small study. This may suggest there would be minimal increases in bleeding risk when either solution is administered to dogs at low doses. Clinical relevance of our findings requires further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 33 publications
0
13
1
Order By: Relevance
“…In two in vitro studies, when whole blood samples were diluted with HES 130/0.4 (1:22, 1:9, 1:4), a hypocoagulable ROTEM tracing was found only at the highest dilution (1:4, mimicking in vivo administration of 30 ml/kg) [ 11 , 14 ]. Whereas, an impairment of secondary hemostasis has been identified after 1:5.5 dilution (comparable to a fluid dose of 20 ml/Kg) using ROTEG analysis [ 12 ]. The results of in vitro studies cannot be directly extrapolated to predict in vivo results, as the effect that a HES solution may have on hemostasis is largely determined by its in vivo pharmacokinetics [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…In two in vitro studies, when whole blood samples were diluted with HES 130/0.4 (1:22, 1:9, 1:4), a hypocoagulable ROTEM tracing was found only at the highest dilution (1:4, mimicking in vivo administration of 30 ml/kg) [ 11 , 14 ]. Whereas, an impairment of secondary hemostasis has been identified after 1:5.5 dilution (comparable to a fluid dose of 20 ml/Kg) using ROTEG analysis [ 12 ]. The results of in vitro studies cannot be directly extrapolated to predict in vivo results, as the effect that a HES solution may have on hemostasis is largely determined by its in vivo pharmacokinetics [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Common to these studies are measurements of platelet function and viscoelastic tests of coagulation. In vitro dilution of canine blood with high MW HES consistently causes hypocoagulability beyond dilution, as measured by TEG (97,98) and ROTEM (27). Two of those studies also assessed platelet function and did not show any effect beyond dilution on PCT (27,98).…”
Section: Hydroxyethyl Starchmentioning
confidence: 98%
“…Other studies measuring PCT have failed to detect an effect beyond dilution with low MW HES (27,29,98). Hypocoagulability beyond dilutional effects has also been demonstrated for low MW HES using TEG or ROTEM in three canine studies (27,37,98), but was not detected in a fourth (51). The only in vitro study of HES dilution of equine blood showed that both high and low MW HES caused significant platelet dysfunction and hypocoagulability, as measured by PCT, TEG, Sonoclot, optical platelet aggregometry, and activities of vWF and FVIII, with many changes in excess of the crystalloid controls (70).…”
Section: Hydroxyethyl Starchmentioning
confidence: 99%
See 2 more Smart Citations